Brill's companion to the reception of Sophocles - Lauriola, Rosanna; Dēmētriou, Kyriakos N. (Brill's companions to classical reception ;, 2017)
"Brill's Companion to the Reception of Sophocles offers a comprehensive account of the influence, reception and appropriation of all extant Sophoclean plays, as well as the fragmentary Satyr play The Trackers, from Antiquity to Modernity, across cultures and civilizations, encompassing multiple perspectives and within a broad range of cultural trends and manifestations: literature, intellectual history, visual arts, music, opera and dance, stage and cinematography. A concerted work by an international team of specialists in the field, the volume is addressed to a wide and multidisciplinary readership of classical reception studies, from experts to non-experts. Contributors engage in a vividly and lively interactive dialogue with the Ancient and the Modern, which, while illuminating aspects of ancient drama and highlighting their ever-lasting relevance, offers a thoughtful and layered guide of the human condition. Contributors are: Simone Beta, Eric Dugdale, Patrick Finglass, Rosanna Lauriola, Enrico Magnelli, Sophie Mills, Elizabeth Scharffenberger, Maria De Fátima Silva and Martina Treu."--